Hubungan Antara Kepatuhan Minum Obat Pada Penderita Kusta dengan Tingkat Kematian di Kabupaten Fakfak Tahun 2022-2024 - Sunartho, Cathleen Pricilia; Hapsari, Retno Niken; Hertanto, Maria Patricia (Jurnal Pendidikan Indonesia, 2025)
Background: Leprosy is an infectious disease caused by the bacterium Mycobacterium leprae. It primarily affects the skin, peripheral nerves, and respiratory tract, leading to neuropathy and long-term consequences, including deformities and disability. It is transmitted through saliva droplets and prolonged close contact with patients. If patients fail to take their medication regularly during leprosy treatment, the leprosy bacteria can become resistant to MDT, potentially leading to treatment failure or even failure to recover. Medication adherence refers to all patients who take their medication regularly until completion of treatment. Objective: This study aims to determine the relationship between medication adherence in leprosy patients and mortality rates in Fakfak Regency. Methods: An observational analytical study with a cross-sectional design was conducted on a total sample of 82 leprosy patients. Data were obtained from the Fakfak Health Office for 2022-2024. Results: The study subjects were 43 (52.4%) male and 39 (47.6%) female. Twenty-eight (82.4%) non-adherent patients died, while six (17.6%) recovered. The chi-square test showed a p-value of 0.000 (p<0.05), indicating a significant relationship between medication adherence in leprosy patients and the mortality rate in Fakfak Regency. Conclusion: There is a relationship between medication adherence in leprosy patients and the mortality rate in Fakfak Regency.